Safety of iodinated contrast media in patients with no risk factorsfor thyroid gland disease: thyroid function assessment after computer tomography with the use of iodine contrast media - Orlicz-Szczęsna, Grażyna; Biłan, Andrzej; Zdanowska, Jolanta (Current Problems of Psychiatry, 2011)
Purpose: A prospective study was performed to assess the influence of single, large iodine dose given intravenously to patients undergoing computer tomography living in areas with sufficient iodine supplementation with table salt.Materials and methods: Thirty one patients with no personal familiar history of thyroid diseases in ages between 22 and 80 years old, were individually given 18.5-55.5 grams of iodine intravenously during computer tomography. Dose of iodine contrast media ranged from 50-150 ml. Evaluated patients had no contact with iodine during the last years. We included patients with no change in thyroid morphology in ultrasound taken by 10 MHz Siemens before trial. In all patients, levels of TSH and FT4 were measured before CT and after 1 and 3 months respectively.Results: Thyroid hormone levels assessed after one and three months were in normal laboratory ranges. Large, single dose of iodine in contrast media caused no disturbances in assessed thyroid hormone levels.Conclusions: In adult patients with no morphologic thyroid gland changes and no disturbances of hormonal function, single large dose of iodine is safe.